Mosquito fauna (Diptera: Culicidae) present in the distinct hydric enclaves of the city of Valencia (Spain) - BUENO-MARÍ, RUBÉN; CORELLA-LÓPEZ, ENRIQUE; JIMÉNEZ-PEYDRÓ, RICARDO (Revista Colombiana de Entomología, 2010)
Over 20 years (1987-2007) a comprehensive monitoring of the larval populations of mosquitoes (Diptera: Culicidae) was conducted in the Municipality of Valencia (Spain) which amounted to the inspection of 667 breeding sites and the collection of 47,131 specimens. Information is provided on the eight species captured, belonging to the genera Culex, Culiseta and Ochlerotatus, and we discuss the lack of findings of Anopheles specimens which were so abundant in the study area during the past. Finally, we also calculated the biodiversity indices of Ribeiro (δ = 3.28) and Shannon (H’ = 1.46) for the family Culicidae in the study area and we postulate anthropization as one of the most important explanatory elements for the loss of biodiversity in these nematoceran diptera.